Helping at awork level 2 book 6 - snowball, Dr Lesley Fern (Karachi : Paramount books ., 2022)
Helping Hand by Lesley Fern Snowball is a simple story about children helping with chores at home. It teaches responsibility, teamwork, and the importance of helping others in everyday life.